The Puesto Piris Formation: Evidence of basin-development in the North Patagonian Massif during crustal extension associated with Gondwana breakup - Strazzere, Leonardo (2019)
The Marifil Volcanic Complex, exposed in the eastern North Patagonian Massif, Argentina, includes up to 550 m of red conglomerates, sandstones, black siltstones, limestones, and reworked tuff of the Puesto Piris Formation. The basal part of this unit, which was deposited in high-gradient topographic relief, is composed of conglomerates and sandstones with thin layers of reworked tuffs. The lithofacies associations of the basal part indicate that the depositional mechanisms were mantled and gravitational flows. The middle part of the unit consists of fine sandstones, limestones, and black siltstones that were deposited in low-energy fluvial and lacustrine environments. The outcrops are located along the NE–SW direction and the major thickest units represented by limestones and siltstones, occur near the southeastern border of this NE–SW depocenter. Since the rhyolitic and trachytic lava flows and tuffs of the Marifil Volcanic Complex are interbedded with the sedimentary sequences of the Puesto Piris Formation, both units are coeval. Zircon U–Pb age was obtained for a trachytic lava flow (193.4 ± 3.1 Ma) suggesting that sedimentation and volcanism are Sinemurian. This extensional episode was recorded in the eastern, western, and southwestern sectors of the North Patagonian Massif, and is possibly associated with the Gondwana supercontinent breakup.